Effectiveness of microcredit program and determinants of income among small business entrepreneurs in Malaysia - Rika Terano; Zainalabidin Mohamed; Jarir Hakimi H. Jusri (Journal of Global Entrepreneurship Research, 2015)
Together with Singapore, Malaysia is one of the successful cases in Asia achieving rapid economic growth. However the issues of poverty still being discussed today. Amanah Ikthiar Malaysia (AIM) is one of the dominant players contributing to the poverty eradication program in Malaysia engaging in microcredit program with supports from Malaysian government. Since microcredit has been effective as a poverty eradication agent among the poor, it is important to investigate the dimension of effectiveness of poverty eradication program carried out by AIM. The objective of this study is to investigate the dimension of effectiveness in microcredit program and to examine the determinants of total income after joining AIM program. Purposive sampling were applied to take a sample of 100 recipients of AIM microcredit program loan in Kuala Selangor, Hulu Langat, and Gombak in Selangor. Descriptive analysis, factor analysis, and multiple linear regression were used as a methodology to achieve the objective of the study. Factor analysis found four dimension of effectiveness in the microcredit program such as earning ability, payment scheme, member's cooperation, and well-being. Similarly regression analysis identified 3 variables that are significantly influence the total income after joining the program. These variables are; duration of loans received, amount of loans and number of employee. There are certain issues that need to be addressed to improve the AIM program especially those related to payment scheme and also finding timing for the recipients to graduate from the program as successful entrepreneurs.
Keywords: 650; Amanah Ikthiar Malaysia (AIM); Microcredit; Poverty; Factor analysis; Regression